Walking in pregnancy and prevention of insomnia in third trimester using pedometers: study protocol of Walking_Preg project (WPP). A randomized controlled trial - C. Amezcua-Prieto; M. Naveiro-Fuentes; N. Arco-Jiménez; R. Olmedo-Requena; R. Barrios-Rodríguez; I. Vico-Zúñiga; S. Manzanares Galán; J. Mozas-Moreno; J. J. Jiménez-Moleón; J. L. Gallo-Vallejo (BMC Pregnancy and Childbirth, 2020)
Abstract Background Previous studies in pregnancy have not focused in evaluating the effect of walking during pregnancy and prevention of insomnia. Our general objective is to determine the effect of a walking program in preventing the appearance of insomnia in the third trimester of pregnancy, increasing sleep quality and improving quality of life throughout pregnancy. Methods Randomized Controlled trial in parallel in healthy sedentary pregnant women (n = 265), Walking_Preg Project (WPP), from university hospital in Granada, Spain. At 12th gestational week (GW), they will be invited to participate and randomly assigned to one of the three arms of study: the intervention group I1 (pedometer, goal of 11,000 steps/day), intervention group I2 (pedometer, no goal) and control (no pedometer). Duration of intervention: 13–32 GW. At 12th, 19th and 31st GW the average steps/day will be measured in groups I1 and I2. At 13th, 20th and 32nd GW, Athens Insomnia Scale (AIS), Pittsburgh Sleep Quality Index (PSQI), Adherence to Mediterranean Diet (AMD), physical activity (short IPAQ), quality of life (PSI), and consumption of toxic substances (caffeine, illegal drugs, alcohol and tobacco) will be collected. Student t test or Mann-Whitney U will be used to compare 19th and 31st GW mean of daily steps between I1 and I2 groups. To compare differences between groups in terms of frequency of insomnia/quality of life for each trimester of pregnancy, Pearson’s Chi-square test or Fisher’s exact test will be used. To determine differences in hours of sleep and quality of sleep throughout each trimester of pregnancy, analysis of variance or Friedman test will be used. McNemar-Bowker test will be used to assess differences in life quality in pre-post analyses in the 3 arms. We will use Stata 15 statistical software. Discussion promoting walking in second half of pregnancy through use of pedometer and health pre-registration of a goal to be achieved –'10,000–11,000 steps a day’– should prevent appearance of insomnia in third trimester, will increase sleep quality and quality of life in pregnant women. Trial registration ClinicalTrials.gov Identifier: NCT03735381 . Registered 8th November, 2018.